The Reactualization of the Murder Payment of Fines (Diyah) in the Aceh Qānūn: A Sociological Perspective of the Islamic Law - Munawarsyah, Munawarsyah; Asmuni, Asmuni; Matsum, Hasan (JURNAL INDO-ISLAMIKA, 2024)
As the only province in Indonesia implementing Islamic Sharia law, Aceh has a rich historical and cultural context rooted in Islamic traditions. In the modern era, understanding how Sharia law interacts with diverse community demands is crucial. This study examines the actualization of diyah (compensation) in Aceh's Qānūn Jināyah (Crimes) using a sociological approach to Islamic law. The qualitative research method employed involves descriptive data collection. The findings reveal that the diyah law in Aceh’s Qānūn Jināyah illustrates the intricate interaction between social, cultural, legal, and religious aspects in the application and acceptance of Islamic law. Diyah serves not only as a formal legal instrument for justice but also as a reflection of the strong cultural values, religious traditions, and social norms within Acehnese society. Through sociological analysis, the study highlights how the mechanism for implementing diyah in the Qānūn Jināyah embodies the integration of Islamic law with the socio-cultural values of Acehnese society, offering insights into how Sharia law adapts to contemporary social challenges and changes.